2021
DOI: 10.1101/lm.052522.120
|View full text |Cite
|
Sign up to set email alerts
|

Better later: evening practice is advantageous for motor skill consolidation in the elderly

Abstract: How does the time of day of a practice session affect learning of a new motor sequence in the elderly? Participants practiced a given finger tapping sequence either during morning or evening hours. All participants robustly improved performance speed within the session concurrent with a reorganization of the tapping pattern of the sequence. However, evening-trained participants showed additional gains overnight and at 1 wk posttraining; moreover, evening training led to a further reorganization of the tapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Moreover, as our study included mainly intermediate-type chronotypes (see also Supplementary results 2 with only intermediate-type participants), Korman et al (2021) showed the same consolidation result after evening training with the morning-type chronotype.…”
Section: The Time-of-day Effects On Skill Acquisitionsupporting
confidence: 57%
See 2 more Smart Citations
“…Moreover, as our study included mainly intermediate-type chronotypes (see also Supplementary results 2 with only intermediate-type participants), Korman et al (2021) showed the same consolidation result after evening training with the morning-type chronotype.…”
Section: The Time-of-day Effects On Skill Acquisitionsupporting
confidence: 57%
“…Skill consolidation according to the time of day is a robust phenomenon and occurs regardless of age and chronotype. Indeed, better consolidation was found after evening training in both adolescent (Holz et al, 2012) and elderly (Korman et al, 2021) populations. Moreover, as our study included mainly intermediate-type chronotypes (see also Supplementary results 2 with only intermediate-type participants), Korman et al (2021) showed the same consolidation result after evening training with the morning-type chronotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skill consolidation according to the time of day does not appear to be population-specific but is a robust phenomenon occurring regardless of age and chronotype. Better consolidation was found after evening training in both adolescent 29 and elderly 72 populations. Moreover, although our study mainly included intermediate-type chronotypes (see also Supplementary notes 3 with only intermediate-type participants), we found a similar conclusion as the study of Korman et al 72 , which showed an advantage in consolidation when the practice was scheduled in the evening for participants with a morning-type chronotype.…”
Section: Discussionmentioning
confidence: 89%
“…As our main research questions focus on the consolidation period (i. . Normalized gains in performance were used in all analyses to control for individual differences in absolute performance levels and allow for a between groups comparison, as was used in previous studies exploring the effect of consolidation on offline gains (Abend et al, 2013;Doyon et al, 2009;Korman et al, 2007Korman et al, , 2021. For each measure we first examined whether participants improved in performance during the total 24 hrs.…”
Section: Language Learning Taskmentioning
confidence: 99%